2007
DOI: 10.1590/s0103-507x2007000400003
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa: freqüência de resistência a múltiplos fármacos e resistência cruzada entre antimicrobianos no Recife/PE

Abstract: A multi-resistência bacteriana tem crescido significativamente nos últimos anos. Entre os gram-negativos a P. aeruginosa demonstra maior facilidade de desenvolvimento de resistência aos antibióticos. O objetivo deste estudo foi determinar os padrões de susceptibilidade antimicrobiana, freqüência de resistência a múltiplos fármacos e de resistência cruzada entre antimicrobianos das cepas de Pseudomonas aeruginosa. MÉTODO: O estudo foi realizado entre setembro de 2004 e janeiro de 2006. Os testes de susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1
14

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 9 publications
2
5
1
14
Order By: Relevance
“…These included the use of very clear definitions for the therapy (empirical, definitive, inappropriate, delayed and combination), definitions for infections according to the NNIS criteria and use of logistic regression [22,29]. Several findings suggest that its results are coherent, such as the inversely proportional relationship between therapeutic adequacy and the likely degree of resistance; the sensitivity pattern for P. aeruginosa, which was very similar to that reported in the MYSTIC study [5] and another study conducted recently in the state of Pernambuco [27]; and, finally, the finding of greater mortality among shock patients and elderly individuals, which is compatible with the literature on severe infections.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…These included the use of very clear definitions for the therapy (empirical, definitive, inappropriate, delayed and combination), definitions for infections according to the NNIS criteria and use of logistic regression [22,29]. Several findings suggest that its results are coherent, such as the inversely proportional relationship between therapeutic adequacy and the likely degree of resistance; the sensitivity pattern for P. aeruginosa, which was very similar to that reported in the MYSTIC study [5] and another study conducted recently in the state of Pernambuco [27]; and, finally, the finding of greater mortality among shock patients and elderly individuals, which is compatible with the literature on severe infections.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, since aminoglycosides were the antimicrobial agents most used in associations and, over the period of this study there was no consensus regarding their use for limited periods, the cause of death could be attributable to their adverse effects. Most of our patients were elderly and kidney failure may have worsened the prognosis for the individuals treated with this medication [ [27] found that the rate of resistance to ciprofloxacin was high, such that it presented activity against only 49.7% of all of the strains of P. aeruginosa and the susceptibility to aminoglycosides was 59.4% for amikacin and 48.6% for gentamicin. Magalhães et al carried out a molecular analysis on 48 strains of P. aeruginosa from Recife/Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Outro antimicrobiano que apresentou grande atividade contra os não fermentadores foi a piperacilina associada ao tazobactam (75,2%), relato semelhante ao encontrado pelos pesquisadores do programa SENTRY (35) , na América Latina, em relação a Pseudomonas aeruginosa, não se afastando também do que foi dito por Figueiredo et al (15) para essa mesma bactéria.…”
Section: Figura -Perfil De Resistência Aos Antimicrobianos De Pacientunclassified
“…Com isso, pode-se perceber que a maioria das amostras foi isolada a partir do material do trato respiratório (68%). Esse fato também foi constatado por Menezes et al (26) , o que de certa forma já era esperado, uma vez que relatamos, em nosso estudo, grande quantidade de cepas isoladas de Pseudomonas aeruginosa, microrganismo comum em patologias respiratórias (13,15,35) . Estudando esse patógeno, encontramos a maioria de cepas provindas do trato respiratório.…”
Section: Figura -Perfil De Resistência Aos Antimicrobianos De Pacientunclassified
See 1 more Smart Citation